The making of the youth: coming of age in Yugoslav cinema - Đurović, Jovana (2020)
This thesis explores representations of young people in four youth films which thematize the coming of age of young adults in 1960s and early 1970s Socialist Federal Republic of Yugoslavia. It is based on the analysis of Čudna devojka/Strange Girl (Jovan Živanović, 1962), Tri sata za ljubav/Three Hours for Love (Fadil Hadžić, 1968) Bubašinter/The Bug Killer (Milan Jelić, 1971), and Kužiš stari moj/Get it, Man (Vanča Kljaković, 1973) that have been made during the so-called utopian phase in Yugoslavia. Cinema is here understood as a privileged domain of youth construction, and a projection of (un)desirable images related to processes of maturing in Yugoslavia. By placing the concept of coming of age at the centre of the analysis, this thesis examines the contradictory relationship between film representations of young people, and the youth ideal promoted by official discourses in Yugoslavia. Close analysis of four films within their specific social, political and cinematographic contexts demonstrates how selected representations subvert society’s main ideological tendencies concerning questions of female emancipation and class liberation.